Towards culturally sensitive public health interventions in Nepal - Sharma, Sudesh Raj; Karki, Neetu (Health Prospect, 2014)
Culture plays a key role in influencing health related behaviours. However, cultural issues are often neglected in public health interventions. The viewpoint attempts to highlight key prerequisites for developing culturally sensitive public health interventions in the context of Nepal. Qualitative research should be promoted to understand the critical link of cultural issues with health problems and tailor interventions accordingly. Making key elements of Behaviour Change Communication (source, message, and channel) process culturally appropriate can render positive effects for health interventions. On an operational level, involving an anthropologist can act as a bridge between community and health workers throughout the implementation process; community organization and empowerment strategies within interventions have proven to be beneficial and sustainable in terms of health promotion and disease prevention. Focusing on developing culturally competent health workforce can produce a synergistic effect in health promotion efforts. To conclude, culturally sensitive interventions should not only be evidence based but empowering and engaging community. DOI: http://dx.doi.org/10.3126/hprospect.v13i1.11104 Health Prospect Vol.13(1) 2014: 1-3